The PVD-Accelerated Soil Deposit Consolidation Based on Elliptic Cylindrical Model - Yulvi Zaika; Gilang R. Kololikiye; . Harimurti (Salehan Institute of Higher Education, 2023)
One method to deal with the problem of soft soil is to accelerate consolidation by preloading and prefabricating a vertical drain (PVD). Consolidation analysis was based on a one-dimensional theory that required PVD as an equivalent circular well. Further studies on a simple approximate for consolidated soil were represented by equivalent permeability coefficients, kve. The equivalent conductivity coefficient is influenced by the soil and PVD permeability coefficients. The formulation of kve based on the influence area in cylindrical has been applied to a lot of construction projects. According to the comparative analysis of the classical consolidation theory, it is considered that the diameter of the circle is less representative. This study proposed a simple formulation of kveÂ based on the elliptical assumption of influence area. The kvewas derived based on an equal average degree of consolidation in one dimension, which applied the elliptical coordinate for degree of consolidation in the radial direction. The formulation is based on an elliptical cross-section and a cylindrical coordinate formulation. The validation of this formula is conducted with numerical calculations using 2D FEM. The results show that the consolidation time in the elliptical discharge area is shorter than that in the circular discharge area.Â Doi: 10.28991/CEJ-2023-09-07-08 Full Text: PDF